2014
DOI: 10.17816/ecogen12139-47
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new genes of nodule bacteria sinorhizobium meliloti involved in the control of efficiency of symbiosis with alfalfa medicago sativa

Abstract: Background. Alfalfa root nodule bacteria (Sinorhizobium meliloti) are among the most active symbiotic N2-fixers. Their symbiotic efficiency (SE) defined as an ability to enhance the productivity of inoculated host plants is the polygenic trait controlled by a complicated system of genes, inactivation of which can result in either decrease or increase of SE. Analysis of previously identified eff-genes, whose mutations result in SE increase, revealed their location in different parts of genome (chromosome or meg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…The standard PCR protocol was used: initial denaturation at 95°C for 3 min, 30 cycles with denaturation at 94°C for 30 s, primer annealing at 48°C for 30 s, extension at 72°C for 1 min, and final extension for 4 min. PCR fragments were extracted from agarose gel (Onishchuk, Chizhevskaya, Kurchak, Andronov, & Simarov, ) and cloned into the plasmid pTZ57R/T (Thermo Scientific). For each plant species, 100 randomly selected cloned fragments of NFR5 genes were sequenced by Sanger method in an automated ABI 3500xL sequencer (Applied Biosystems) using standard M13 (−20) and (−26) primers.…”
Section: Methodsmentioning
confidence: 99%
“…The standard PCR protocol was used: initial denaturation at 95°C for 3 min, 30 cycles with denaturation at 94°C for 30 s, primer annealing at 48°C for 30 s, extension at 72°C for 1 min, and final extension for 4 min. PCR fragments were extracted from agarose gel (Onishchuk, Chizhevskaya, Kurchak, Andronov, & Simarov, ) and cloned into the plasmid pTZ57R/T (Thermo Scientific). For each plant species, 100 randomly selected cloned fragments of NFR5 genes were sequenced by Sanger method in an automated ABI 3500xL sequencer (Applied Biosystems) using standard M13 (−20) and (−26) primers.…”
Section: Methodsmentioning
confidence: 99%
“…The standard PCR protocol used consisted of initial denaturation at 95°C for 3 min, 30 cycles with denaturation at 94°C for 30 s, primer annealing at 48°C for 30 s, extension at 72°C for 1 min and final extension for 4 min. PCR fragments were extracted from agarose gel (Onishchuk et al, 2015 ) and cloned into the plasmid pTZ57R/T (Thermo Scientific, Lithuania).…”
Section: Methodsmentioning
confidence: 99%
“…Identification of Tn5-tagged genes was carried out using the inverted polymerase chain reaction technique (Onishchuk et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, activation of phosphoenolpyruvate carboxykinase in bacteroids leads to a 70 % reduction of N 2 -fixing activity compared to wild-type bacteroids (Mulley et al, 2010), suggesting that operation of this enzyme is disadvantageous for the symbiosis operation. Earlier, we revealed in alfalfa rhizobia (Sinorhizobi um meliloti) a number of eff genes whose inactivation by Tn5 insertions leads to an increased symbiotic efficiency (SE) -the impact of bacteria inoculation on host plant productivity (Sharypova et al, 1994;Onishchuk, Sharypova and Simarov, 1994). Among these genes, addressed as the negative regulators of symbiosis (Provorov et al, 2014), several groups were identified as being involved in: (i) accumulation of storage nutrients (glycogen, GABA), which reduces the catabolic activity of bacteroids; (ii) negative control of respiration, which restricts the energy flow to nitrogenase; (iii) synthesis of surface polysaccharides, which elicit host defense reactions, thereby reducing the persistence of the endo-symbiotic bacterial population.…”
Section: Symbio-geneticsmentioning
confidence: 99%